Modelling Income Using the Generalised Lambda Distribution - Haridas, Haritha N.; Nair, N. Unnikrishnan; Nair, K.R. Muraleedharan (Journal of Income Distribution®, 2008)
In the present article we propose the generalised lambda distribution as a model for income data. The quantile measures of location, dispersion, skewness, and kurtosis of the distribution are matched against the corresponding measures derived from the sample to estimate the parameters of the model. It is shown that the distribution provides reasonable fit to real data. Some properties of the model, including measures of income inequality, are also discussed in the article. Comparison of the generalised lambda distribution fits with other models is made.